Synthesis of Hydroxyapatite From Egg Shells Using Precipitation Methods For Bone Implant Application - Veni Wahyuni; Riri Jonuarti; Ratnawulan; Rahmat Hidayat (Journal of Experimental and Applied Physics, 2023)
Patients with fractures continue to increase from year to year. So that the need for biomaterials is very high and has had a considerable impact, especially in the field of orthopedic medicine. Hydroxyapatite (HAp) is one of the suitable biomaterials for bone implants. Hydroxyapatite (HAp) with the chemical formula C10(PO4)6O2H2 is a calcium phosphate that contains hydroxide, which is classified as a mineral in the apatite group. HAp can be obtained from natural waste such as the eggshells of a chicken. This is because chicken eggshells have a very high CaO content (98,43%) which serves as a precursor in the synthesis of HAp. The purpose of this research the aim of observing the effect of stirring time on the purity of the HAp produced and to see the optimum stirring time used to produce good HAp. In this study, HAp was synthesized using a precipitation method by varying the stirring time. Based on variations in stirring time of 1 hour, 2 hours, 3 hours, 4 hours, and 5 hours, the purity of HAp obtained was 15%, 49%, 66%, 82%, and 50%, respectively. Therefore, it was concluded that the optimal stirring time to produce HAp with the highest purity is at a time interval of 4 hours.